Paepalanthus mellosilvae (Eriocaulaceae), a new species from the Mantiqueira Range in Minas Gerais, Brazil - Trovó, Marcelo (Phytotaxa, 2021)
Paepalanthus mellosilvae is here described and illustrated as a new species of Eriocaulaceae from the Atlantic Forest domain in Minas Gerais state, Brazil. The new species is known from a single locality in the Mantiqueira Range, growing along trails through cloud forests. According to the IUCN criteria, it is suggested here as critically endangered. Paepalanthus mellosilvae is compared to P. harmsii, a morphologically similar species also growing in the Mantiqueira Range, being mainly distinguished by the presence of a rhizome, narrower leaves, more numerous scapes, narrower capitula, sparsely pilose involucral bracts, and obdeltate floral bracts. Additional comments on the taxonomy, morphology, and distribution of the species, along with illustrations are provided. The specific epithet is a tribute to Prof. Dr. Renato de Mello-Silva.